DIVERSIDAD Y ABUNDANCIA DE MALEZAS ASOCIADAS AL CULTIVO DE CACAO (Theobroma cacao L.) EN TRES ZONAS DEL TRÓPICO ECUATORIANO - Muñoz Ronquillo, Mary Paz (2023)
Ecuador holds fourth place worldwide in cocoa production and first place as the main producer of fine aroma cocoa. Weeds, in the agronomic sense, represent plants without economic value, affecting their production and development capacity, this indicates that weeds represent one of the severe problems of agriculture. The objective of this research was based on identifying the community of weeds associated with the cultivation of cocoa (Theobroma cacao L.).